Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/aro2.10
|View full text |Cite
|
Sign up to set email alerts
|

Zinc methionine improves the lipid metabolism that is associated with the alteration of intestine mucosal proteomes and microbiota of newborn Holstein dairy calves

Abstract: Supplementation of diets with a modest amount of zinc methionine (ZM) has been documented to improve the growth performance and antioxidant function of dairy calves, but the underlying mechanisms remain elusive. In the present study, 16 dairy calves were allocated to a control (CON) group (calves consumed a basal diet) and a ZM group (calves ingested the basal diet and had an additional 455 mg ZM/day, corresponding to 80 mg zinc/day). The calves were fed these diets for 2 weeks, after which their serum antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Short et al [12] found that GOS increased the apparent efficiency of absorption of IgG in calves by 20% compared to the control group. Mineral deficiencies in young animals may lead to growth retardation and deficiency, but supplementation with GOS can promote the absorption of minerals such as calcium, iron, zinc, and magnesium [13][14][15][16][17][18][19][20]. Chang et al [21] found that GOS significantly increased the serum calcium concentrations in calves.…”
Section: Introductionmentioning
confidence: 99%
“…Short et al [12] found that GOS increased the apparent efficiency of absorption of IgG in calves by 20% compared to the control group. Mineral deficiencies in young animals may lead to growth retardation and deficiency, but supplementation with GOS can promote the absorption of minerals such as calcium, iron, zinc, and magnesium [13][14][15][16][17][18][19][20]. Chang et al [21] found that GOS significantly increased the serum calcium concentrations in calves.…”
Section: Introductionmentioning
confidence: 99%